Molecular and epidemiological surveillance of polymyxin-resistant Klebsiella pneumoniae strains isolated from Brazil with multiple mgrB gene mutations - Kesia Esther da Silva; To Nguyen Thi Nguyen; Christine J. Boinett; Stephen Baker; Simone Simionatto (Elsevier, 2020)
The prevalence of polymyxin-resistant Enterobacteriaceae is increasing worldwide. Their emergence is worrisome and limits therapeutic options for severely ill patients. We aimed to investigate the molecular and epidemiological characteristics of polymyxin-resistant Klebsiella pneumoniae circulating in Brazilian hospitals. Polymyxin-resistant K. pneumoniae isolates from two Brazilian healthcare facilities were characterized phenotypically and subjected to whole genome sequencing (WGS). Using the WGS data we determined their sequence type, resistance gene content (resistome), their composition of virulence genes and plasmids. ST11 was the most common (80 %) sequence type among the isolates followed by ST345, ST15 and ST258. A resistome analysis revealed the common presence of blaKPC-2 and less frequently blaSHV-11, blaTEM-1, blaCTX-M-15, and blaOXA-9. Genes conferring resistance to aminoglycosides, fluoroquinolones, phenicols, sulphonamides, tetracyclines, trimethoprim and macrolide-lincosamide-streptogramin were also detected. We observed a clonal spread of polymyxin-resistant K. pneumoniae isolates, with polymyxin-resistance associated with various alterations in the mgrB gene including inactivation by an insertion sequence and nonsense point mutations. We additionally identified a novel 78-bp repeat sequence, encoding a MgrB protein with 26 amino acids duplicated in six isolates. This is the first observation of this type of alteration being associated with polymyxin resistance. Our findings demonstrate that mgrB alterations were the most common source of polymyxin-resistance in Brazilian clinical settings. Interestingly, distinct genetic events were identified among clonally related isolates, including a new amino acid alteration. The clinical implications and investigation of the resistance mechanisms is of great importance to patient safety and control of these infections, particularly in long-term care facilities.